Earthquake scientific literacy profile of Indonesian first year pre-service physics teacher - Deta, Utama Alan; Sasmi, Rinda Rahmanisa; Arisanti, Aini; Laila, Luthfiyaul; Hudha, Muhammad Nur; Mubarok, Husni; Prahani, Binar Kurnia; Suprapto, Nadi (Intelektual Pustaka Media Utama, 2025)
In higher education, fostering scientific literacy stands essential, especially in understanding and responding to natural disasters. This research investigates the scientific literacy levels among Physics Education students at State University in Surabaya, Indonesia, focusing on earthquake disaster mitigation. This study uses a qualitative descriptive approach that engaged 102 first-year pre-service teachers through a meticulously designed literacy test based on a new programme for international student assessment (PISA) framework 2025. The findings reveal a commendable proficiency in explaining scientific phenomena utilizing scientific knowledge. However, it uncovers a gap in students' abilities to make informed decisions in the context of earthquake disaster mitigation. This drawback is attributed to a lack of comprehensive literacy concerning disaster news, impacts, and mitigative strategies. Despite this, students demonstrated a capacity to argue and articulate their understanding logically based on existing knowledge. The study accentuates the need to enhance students' literacy and decision-making skills regarding natural disasters, advocating for heightened self-awareness and educational interventions to empower students to make informed decisions in disaster-prone scenarios.